Membangun Budaya Anti Korupsi di Desa Buyumpondoli : Strategi Edukasi dan Partisipasi Masyarakat - Septian Aditya Kolompo; Astina Sofianti Jende; Rick Rare’a; Angela Veronika Tohoro; Mersy Yunita Wutabisu; Cherlis Pesoyoki; Chikal Pamuna; Miranda Sintagi; Mersi Tineke Ulungi; Michael Taaha; Selwi Kamagi; Angelin Tarusu; Feliks Arfid Guampe (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
This Community Service Program (PKM) aims to develop an anti-corruption culture in Buyumpondoli Village, Pamona Puselemba District, through socialization activities targeting village officials and the community. The activity was conducted by a team consisting of lecturers and students from Universitas Kristen Tentena throughout April 2025. The implementation method consisted of three main stages: preparation, implementation, and evaluation. During the preparation stage, initial observations, program planning, and technical arrangements were carried out. The socialization involved the Head of the Poso District Attorney’s Office in Tentena as the main speaker, covering fundamental concepts of corruption, types of corruption, legal sanctions, anti-corruption values, and reporting mechanisms. Evaluation was conducted by monitoring participant engagement and completing the anti-corruption village instrument. The results showed an increase in the understanding of both village officials and the community regarding the importance of building an anti-corruption culture, as well as growing awareness of the need for transparent and accountable village governance. This activity serves as an initial foundation for the development of a continuous mentoring program aimed at achieving an anti-corruption culture in the future.